Retracted : The Link Between Budget Deficit and Current Account Deficit in India. Issue 4 (January 2016) - Aneja, Ranjan; Banday, Umer Jeelanie
At the request of the Journal Editor and the Authors, the following article has been retracted. Aneja, R., & Banday, U. J. (2015). The link between Budget deficit and Current Account deficit in India. Journal of the Indian Economic Association 63(4), 750–761. DOI: 10.1177/0019466220160411 The article has been retracted from The Indian Economic Journal as the authors had not provided the due permission for its publication. The said article is now duly published in another journal.